The effect of emicizumab prophylaxis on health‐related outcomes in persons with haemophilia A with inhibitors: HAVEN 1 Study. Issue 1 (14th November 2018) - Oldenburg, Johannes; Mahlangu, Johnny N.; Bujan, Willem; Trask, Peter; Callaghan, Michael U.; Young, Guy; Asikanius, Elina; Peyvandi, Flora; Santagostino, Elena; Kruse‐Jarres, Rebecca; Negrier, Claude; Kessler, Craig; et al.
Abstract : Introduction: Persons with haemophilia A (PwHA) with inhibitors to factor VIII often experience decreased health‐related outcomes. In HAVEN 1 (NCT02622321), there was a statistically significant reduction in bleeding with emicizumab prophylaxis versus no prophylaxis. Aim: Describe health‐related outcomes in PwHA with inhibitors in HAVEN 1. Methods: PwHA with inhibitors aged ≥12 years previously on episodic bypassing agents (BPAs) were randomized to emicizumab prophylaxis (Arm A; n = 35) or no prophylaxis (Arm B; n = 18); participants previously on BPA prophylaxis received emicizumab prophylaxis (Arm C; n = 49). Health‐related outcomes assessed at baseline and monthly thereafter: Haemophilia Quality of Life Questionnaire for Adults (Haem‐A‐QoL), Haemophilia‐specific Quality of Life Questionnaire for Children Short Form (Haemo‐QoL SF), EuroQol 5‐Dimensions 5‐Levels (EQ‐5D‐5L) index utility score (IUS) and visual analogue scale (EQ‐VAS) and work/school days. Days hospitalized also recorded. Results: At week 25, differences (ANCOVA) in adjusted mean scores (95% confidence interval) favoured Arm A versus B for Haem‐A‐QoL "Total" score (14.0 [5.6, 22.5]; P = 0.002) and "Physical Health" (21.6 [7.9, 35.2]; P = 0.003); EQ‐VAS (−9.7 [−17.6, −1.82]; P = 0.017); and IUS (−0.16 [−0.25, −0.07]; P = 0.001); mean scores are comparable in Arms A and C. Throughout the study, a greater proportion of participants on emicizumab prophylaxis than no prophylaxis exceeded questionnaire‐specific responder thresholds. Mean proportion of missed work days and number of days hospitalized were lower with emicizumab prophylaxis than no prophylaxis. Conclusions: In PwHA with inhibitors, emicizumab prophylaxis was associated with substantial and meaningful improvements in health‐related outcomes.